If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -4) = 2x + -5(x + 2) Reorder the terms: -1(-4 + x) = 2x + -5(x + 2) (-4 * -1 + x * -1) = 2x + -5(x + 2) (4 + -1x) = 2x + -5(x + 2) Reorder the terms: 4 + -1x = 2x + -5(2 + x) 4 + -1x = 2x + (2 * -5 + x * -5) 4 + -1x = 2x + (-10 + -5x) Reorder the terms: 4 + -1x = -10 + 2x + -5x Combine like terms: 2x + -5x = -3x 4 + -1x = -10 + -3x Solving 4 + -1x = -10 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + -1x + 3x = -10 + -3x + 3x Combine like terms: -1x + 3x = 2x 4 + 2x = -10 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + 2x = -10 + 0 4 + 2x = -10 Add '-4' to each side of the equation. 4 + -4 + 2x = -10 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = -10 + -4 2x = -10 + -4 Combine like terms: -10 + -4 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| -5(4r-4)-4r=-172 | | W=150*10 | | -2r-10=-37 | | -15-7z=-14-7z | | (-5m^2-6m-6)-(5m^2+6m+2)= | | 5y+6=6y-5 | | 4x+10=6x-24 | | log9/8 | | 7(x+20)-10=x+4 | | 8t^2+9t-5=0 | | 3(11+3x)=3(-1+5x) | | (z+1)=2(3-2z)+17 | | 16x+10+5x+2=180 | | 32=3x+9 | | (4x-20)= | | y-x=32 | | ((9x-11)+(7x-3))=((4x+1)(4x+1)) | | -9x-3x+4=-10x-(2x-4) | | 288=27x+18 | | 5(2h+3)-4h= | | 90=-5x-5(x-8) | | -8x+9=2x+49 | | 2x-5-4x=17 | | 11+20x=22x-1 | | 20/258 | | -x+4q=41 | | A=77-14.99n | | 9b+4=-23 | | 0=9-1/50x^2 | | -201=4n+7(1-8n) | | -3x-5(x-2)=4 | | 8r^4-r^2= |